2013
DOI: 10.1111/jph.12087
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli Stunt, a New Disease in Broccoli Plants Associated with Three Distinct Phytoplasma Groups in Brazil

Abstract: Since 2007, a new disease in broccoli (Brassica oleracea var. italica Plenck) has been observed in the São Paulo state, Brazil. The characteristic symptoms of the disease are plant stunting, inflorescence malformation, reddening of the leaves and phloem necrosis. Nested polymerase chain reaction with P1/Tint and F2n/R2 primer pairs revealed the presence of phytoplasmas in diseased broccoli plants. Restriction fragment length polymorphism and phylogenetic analysis of the 16S rDNA gene showed that phytoplasmas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…In these cases, although representatives of the 16SrI group have been reported (Eckstein et al. ), phytoplasmas affiliated with the 16SrIII group were most frequently found in diseased plants.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In these cases, although representatives of the 16SrI group have been reported (Eckstein et al. ), phytoplasmas affiliated with the 16SrIII group were most frequently found in diseased plants.…”
Section: Introductionmentioning
confidence: 92%
“…The affected plants are unmarketable, ultimately resulting in economic losses for growers. A variety of economic species has been cultivated in this region of the state of São Paulo, and previous studies showed that mainly vegetable crops were affected by diseases associated with phytoplasmas, including eggplant (Amaral-Mello et al 2011), cauliflower (Rappussi et al 2012, broccoli (Eckstein et al 2013) and cassava (Flôres et al 2013). In these cases, although representatives of the 16SrI group have been reported (Eckstein et al 2013), phytoplasmas affiliated with the 16SrIII group were most frequently found in diseased plants.…”
Section: Introductionmentioning
confidence: 98%
“…The in silico restriction analysis (RFLP) carried out with the online tool iPhyClassifier showed a cleavage pattern identical to the reference pattern for the 16SR XIII subgroup F (GenBank: KJ921641) ( Figure 4). The 16SrXIII group is present in region of South America affecting various crops such as potatoes (Solanum tuberosum L.), broccoli (Brassica oleracea L.), strawberry (Fragaria ×ananassa Duchesne ex Rozier) and papaya (Carica papaya L.), among others (Santos-Cervantes et al, 2010;Eckstein et al, 2013;Melo et al, 2013;Fernández et al, 2015). Results shown in this study indicate that the group 16SrXIII-F also affects Berberidaceae family, and therefore is added to the number of reports that indicate the presence of phytoplasmas in diverse crops from Chile such as natives plants (Arismendi et al, 2010a) and fruit trees (Gajardo et al, 2009;González et al, 2011).…”
Section: Identification Of Phytoplasmamentioning
confidence: 99%
“…Affected plants exhibit stunting, inflorescence malformation, reddening leaves and vessel necrosis. In previous studies performed with broccoli plants sampled in the green belt area, it was demonstrated the presence of phytoplasma of 16SrIII group (“ Candidatus Phytoplasma pruni” ‐ Davis et al., ) in association with the diseased plants (Eckstein et al., ). However, the phytoplasma was not identified to level of subgroup.…”
Section: Introductionmentioning
confidence: 98%
“…However, the phytoplasma was not identified to level of subgroup. The disease causes yield losses that range from 3% to 10% (Eckstein et al., ). Phytoplasmas belonging to 16SrIII were also reported in other species of cruciferous such as cabbage (16SrIII‐subgroup not identified) (Mello, ) and cauliflower (16SrIII‐J) (Rappussi et al., ) grew in commercial fields.…”
Section: Introductionmentioning
confidence: 99%